Modeling Lamellar Cracks. - Jaroniek, Mieczysław; Niezgodziński, Tadeusz (Lodz University of Technology. Faculty of Mechanical Engineering. Department Division of Dynamics., 2013)
In this work, studies of models simulating lamellar cracks were conducted. These cracks are formed in rolled sheets with non-metallic inclusions. Studies of lamellar cracks began in the 1960s, but there is still no satisfactory theory explaining their formation. In this work, the application of modeling of samples with non-metallic inclusions for the study of lamellar cracking has been presented. Studies were conducted using two research methods: the photoelastic method and the finite element method. The possibility of crack formation was analyzed in models generated from images obtained from metallographic specimens.
Keywords: non-metallic inclusions; photoelastic tests; finite element method; lamellar cracking; wtrącenia niemetaliczne; testy fotoelastyczne; metoda elementów skończonych; pęknięcia lamelarne